Everyday Pain in Three- to Five-Year-Old Children in Day Care - Carl L von Baeyer; Shannon Baskerville; Patrick J McGrath (Pain Research and Management)
A new event sampling instrument, the Dalhousie Everyday Pain Scale, was used to observe 50 children in six day care centres in Saskatoon for an average of 2.24 h each. The nature of minor painful incidents (eg, collisions and falls) was recorded, including distress behaviours and responses from peers and adults. Twenty-nine children (58%) were observed to experience one or more painful incidents, producing a total of 51 incidents and yielding a median rate of incidents of 0.31 per child per hour, a rate similar to that reported in another Canadian sample. Seven of nine child response items met criteria for reliability in a subsample of incidents observed simultaneously by two observers. Rubbing the affected body part, crying and making verbal statements about the injury were the most common responses to painful incidents. Intervention by day care staff was strongly associated with children's facial expression of distress: physical and first aid interventions were offered most frequently to children who displayed the greatest facial distress. Content analysis of observers' records produced a classification scheme for causes of painful incidents. Twenty per cent of painful incidents were judged to be the result of deliberate actions by other children. The classification of causes may be a useful addition to the scale for application in future studies of everyday pain and injury prevention.